Kajian toleransi antar umat beragama pada masyarakat keturunan Portugis di Kampung Tugu Jakarta Utara - Reza Maulana (CIVICS: Jurnal Pendidikan Pancasila dan Kewarganegaraan, 2021)
This study aims to understand, describe, and analyze data and facts regarding to the values ​​of tolerance in inter-religious community done by Portuguese descent in Kampung Tugu to the other people near the village with different religion. In addition, this research was conducted to find out the implementation of the tolerance values of the Portuguese descent in Kampung Tugu towards the surrounding residents with different religions. The type of research used in this study is qualitative research with a descriptive approach. The data collection techniques are in the form of observation, in-depth interviews, document studies, and audio-visual materials. The data calibration technique used in this study is member check. Audit trail, triangulation, and expert opinion. In addition, the data analysis techniques used are data reduction, data presentation, and drawing conclusions or generalizations. This study concluded that the implementation of tolerance values through art and culture instrument is done by using keroncong music and traditional custom, such as rabu-rabu and mandi-mandi as the media of gathering among the community members to know and understand tbe existing differences.